Bem-estar e cuidado em famílias neurodiversas: o papel das práticas integrativas na qualidade de vida de pais e cuidadores de crianças neurodivergentes - Xavier, Viviane Aleixo de Paula (Universidade Estadual de Ponta Grossa (UEPG), 2026)
Caregivers and family members of neurodivergent children face ongoing challenges that can compromise their physical and emotional health, directly affecting the quality of care provided. The burden generated by the demands of care, coupled with concern for the child's future, scarcity of social support, and financial difficulties, contributes to increased levels of stress, anxiety, and emotional exhaustion. In this context, Integrative and Complementary Health Practices (ICPs) have been recognized for their potential to promote well-being and manage psychological symptoms. This study aimed to understand how participation in a 12-session program using ICPs influences the perception of quality of life of parents and caregivers of neurodivergent children. This is a longitudinal study, with a quantitative and qualitative approach, conducted through a randomized clinical trial with 12 participants, divided into an Intervention Group (IG) and a Control Group (CG). The WHOQOL-Bref, Beck Anxiety Scale, and Perceived Stress Scale-10 instruments were used, in addition to a sociodemographic questionnaire and a semi-structured interview with the participants in the intervention group. Quantitative results indicated a statistically significant improvement in the perceived quality of life of the participants in the intervention group, especially in the psychological, physical, and social relationship domains. A significant increase was observed in the psychological domain (mean difference of 25 points; p < 0.001), reflecting improvements in self-esteem, emotional regulation, and stress coping. Significant gains were also observed in the physical (p = 0.010) and social relationship (p = 0.025) domains, as well as a consistent reduction in perceived stress and anxiety levels, as measured by the Beck Anxiety Scale (mean reduction of 10.17 points). This research contributes to the advancement of knowledge about psychosocial interventions aimed at neurodiverse families, highlighting the relevance of Integrative and Complementary Practices (PICs) as tools for promoting mental health, resilience, and quality of life.
Keywords: saúde mental; autocuidado; promoção da saúde; rede de apoio; resiliência